If 3 zeros of the polynomial f ( x ) = x 4 + a x 2 + b x + c are 2 , − 3 , and 5 , then find the value of a + b + c .
This prob is a part of the set NMTC Practice Problems
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Beautiful approach. Thanks..
Excuse me, I didn't understand how we can realize that a + b +c = f(1) - 1 . Could you explain, if you may? Thanks in advance!
Log in to reply
f(1) allways gives the sum of all coefficiens. In his problem, f(1)=1+0+a+b+c, So f(1)-1=a+b+c. f(0) allways gives the constant term. Say here f(0)=c..
polynomial has 4 roots 2,-3,5 and let 4th root be d.
then poly=
f(x)= (x-2)(x+3)(x-5)(x-d)
multiply this and equate coefficient of x^2 to 0. you will get d= -4. put this in f(x) and get a= -27, b= -14 and c=120
a+b+c =79
1 5 1 6 f ( 2 ) + 1 0 1 f ( − 3 ) − 6 1 f ( 5 ) = − 7 9 + a + b + c = 0 ⟹ a + b + c = 7 9
From vieta we can find the fourth root which is − 4 . Now f ( x ) = ( x − 2 ) ( x + 3 ) ( x − 5 ) ( x + 4 ) We observe that f ( 1 ) = ( − 1 ) ( 4 ) ( − 4 ) ( 5 ) = 8 0 = 1 + a + b + c ⇒ a + b + c = 7 9
Sir, How did you find out that the 4th root is -4?
Problem Loading...
Note Loading...
Set Loading...
The polynomial is ( x − 2 ) ( x + 3 ) ( x − 5 ) ( x + 4 ) by Vieta. Then a + b + c = f ( 1 ) − 1 = ( 1 − 2 ) ( 1 + 3 ) ( 1 − 5 ) ( 1 + 4 ) − 1 = 7 9 . No need to actually find a , b , c .